Estudo do potencial cardiomiogênico de células-tronco mesenquimais - Juliana Lott de Carvalho (2011)
Even though mesenchymal stem cell differentiation towards osteogenic, chondrogenic and adipogenic lineages has been extensively described in the literature, cardiomyogenic differentiation remains largely controversial. In one hand several authors claim that they achieved cardiomyogenic differentiation in vitro, on the other hand, some authors question the reproducibility of the results and the lack of functional essays. Published papers study different cell populations, differentiation and testing techniques, rendering the comparison among them impossible. In order to shed light into this unclear phenomenon and find out the real cardiomyogenic potential of mesenchymal stem cells, the present study induced the cardiomyogenic differentiation of mesenchymal stem cells isolated from the bone marrow and adipose tissue of wistar rats using two published differentiation protocols. The results obtained allow to suggest that the MSC responded to the stimuli present in the inductive media, as they presented a similar phenotype compared to cardiomyocytes: MSC presented lower levels of proliferation, alkaline phosphatase and collagen production, began to express transcription factors such as GATA-4 and Nkx2-5, and genes such as and -MHC. The levels presented by differentiated MSC, never the less, were lower than the levels presented by neonatal and adult cardiomyocytes. MSC also presented phenotypic profile similar to cardiomyocyte published profile: CD45-, CD54low, CD73positive or negative and CD90-. Even though the expression of CD45 raised in some conditions and the expression of CD90 did not lowered through differentiation process none of such results are incompatible with the cardiomyogenic phenotype. In agreement with such argument, differentiated MSC presented sarcomeric -actinin and connexin-43 correctly located in the cell, indicating the possibility of a complete and functional differentiation. MSC did not show electrophysiology properties of fuctional cardiomyocytes, though. Not only they did not show inward and outward currents but, consequently, they also did not developed action potentials when stimulated. Taken together, the present data allow to suggest that MSC induced to follow cardiomyogenic differentiation originated non-functional cardiomyocytes in vitro. For the first time it was demonstrated that the peaks of expression of Nkx2-5, and -MHC in differentiated MSC do not reach expression levels of functional cardiomyocytes. Such observation underscores the importance of quantitative techniques in order to prevent misguided interpretations, as well as the paramount role of positive and negative controls. Nowadays, the sensibility of many techniques is extremely high, and even biologically irrelevant signals are detected.